The effects of water soaking and low temperature on germination of Eleusine indica / Fatin Farhanah Mohd Naim - Mohd Naim, Fatin Farhanah (Faculty of Plantation and Agrotechnology, 2018)
The purpose of this study was to determine the best treatment for enhancing seed germination of Eleusine indica in evaluating its invasiveness in field. It is because the seeds have dormancy and need to undergo certain scarification techniques. Scarification is the process that will break the dormancy of the seeds involving weakening, opening, or otherwise altering the coat of a seed to encourage germination. In the current study, E. indica seeds were first air-dried for one week. Seed moisture content (MC) was determined. Then, freezer incubation at -20C, refrigerator incubation at 5C and water soaking were conducted. Frozen seeds were thawed at ambient temperature prior to seed germination test. Control seeds, on the other hand, were those germinated directly without any treatment. Each treatment was replicated three times with 50 seeds per replicate. The seeds were germinated on moist paper towel in petri dishes. Germinated seeds were recorded and removed daily. Results showed that the best treatment, as indicated by germination percentage and germination index, was refrigeration. Freezing followed by thawing and water soaking also gave good seed germination. Scarification methods with different temperatures were able to break the seed dormancy. In addition, chemical seed germination inhibitor like abscisic acid, which delays seed germination, is presumed to be present on seed. It could be overcome with water soaking. This can be achieved in nature with rain and leaching.